Primary testicular carcinoid tumor with marked lymphovascular invasion - Hyun Jung Lee; Joon Young Park; So Young Kim; Chung Su Hwang; Jung Hee Lee; Dong Hoon Shin; Jee Yeon Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Testicular carcinoid tumors are very rare, accounting for less than 1% of all testicular tumors. We report a rare case of a testicular carcinoid tumor with extensive lymphatic invasion. A 42-year-old man presented with a painless, enlarged right testicular mass. There was no history of injury or discomfort in this region. Right radical orchiectomy was performed, which showed a well-defined, non-encapsulated solid white mass with calcification (7.0 × 4.5 × 3.5 cm) and absence of cystic components. Microscopic examination using hematoxylin and eosin staining of the tumor sections identified organoid, trabecular, and solid patterns with rosette formation. Extensive multifocal lymphatic invasion was observed. Immunohistochemistry was positive for synaptophysin, chromogranin, and CD56. Testicular carcinoid tumors usually show good prognoses; however, there was extensive lymphovascular invasion in this case. Thus, in the case of unusual presentation of the disease, close follow-up is necessary.